Air passenger traffic and local employment: Evidence from Turkey - Özcan, İsmail Çağrı (European Journal of Transport and Infrastructure Research, 2013)
By providing fast and safe transportation opportunities, air transportation plays an important social and economic role in the development of cities and the nation as a whole. Using Census 2000 data from 31 provinces, this study attempts to figure out the possible effects of air passenger traffic on the local composition of employment in Turkey. Its results suggest that employment in many industries and occupations benefits from the existence of scheduled air passenger traffic. More concretely, we found that a 10% point increase in air passenger traffic per capita would generate 15,013 service-related jobs throughout the 31 provinces analysed.